2014
DOI: 10.3109/0886022x.2013.875815
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of volume overload by bioelectrical impedance analysis, NT-proBNP and inferior vena cava diameter in patients with stage 3&4 and 5 chronic kidney disease

Abstract: Results: Overhydration was more frequent in Stage 5 than in Stages 3&4 patients. Systolic and diastolic blood pressure, inferior vena cava index, and log NT-proBNP were higher in overhydrated compared to non-overhydrated patients. A significant positive correlation existed between overhydration/extracellular water and log NT-proBNP, systolic and diastolic blood pressures, and inferior vena cava index. In multiple linear regression analysis, the variables associated with hydration status were male sex, extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…In this study, we used the BCM, mostly utilized in dialysis patients, and found that about half of our patients, predominantly in stages 3 and 4, were considered overhydrated, but we did not observe any association with hypertension. Different from our results, a study with patients in stages 3 and 4 found that a significant positive correlation existed between overhydration, systolic and diastolic blood pressures [38]. Traditionally, the volume change mediated by the renin-angiotensin-aldosterone system is related to the effect of sodium intake on BP; however, studies have indicated other mediators with a more important role in volume overload as vascular stiffness or inflammation [39,40].…”
Section: Discussioncontrasting
confidence: 54%
“…In this study, we used the BCM, mostly utilized in dialysis patients, and found that about half of our patients, predominantly in stages 3 and 4, were considered overhydrated, but we did not observe any association with hypertension. Different from our results, a study with patients in stages 3 and 4 found that a significant positive correlation existed between overhydration, systolic and diastolic blood pressures [38]. Traditionally, the volume change mediated by the renin-angiotensin-aldosterone system is related to the effect of sodium intake on BP; however, studies have indicated other mediators with a more important role in volume overload as vascular stiffness or inflammation [39,40].…”
Section: Discussioncontrasting
confidence: 54%
“…In a multicentre study in prevalent dialysis patients, the mean level of FO in HD patients, assessed by the same methodology, was 1.7 L [ 20 ]. A smaller study of Yilmaz et al has also shown that abnormalities in indicators of FO already are observed before the start of dialysis, which appears to be related to the severity of the CKD stage [ 21 ]. This study of Yilmaz et al observed a mean level of FO, assessed by the same methodology, of 3.9 L in 68 non-dialysed CKD stage 5 patients [mean estimated glomerular filtration rate (eGFR) 8.8 mL/min/1.73 m 2 ], when compared with 2.3 L in 62 CKD stage 3–4 (mean GFR 28.9 mL/min/1.73 m 2 ) [ 21 ], both higher when compared with the levels in the dialysis population studied by van Biesen et al [ 20 ].…”
Section: Cardiovascular Parametersmentioning
confidence: 99%
“…A smaller study of Yilmaz et al has also shown that abnormalities in indicators of FO already are observed before the start of dialysis, which appears to be related to the severity of the CKD stage [ 21 ]. This study of Yilmaz et al observed a mean level of FO, assessed by the same methodology, of 3.9 L in 68 non-dialysed CKD stage 5 patients [mean estimated glomerular filtration rate (eGFR) 8.8 mL/min/1.73 m 2 ], when compared with 2.3 L in 62 CKD stage 3–4 (mean GFR 28.9 mL/min/1.73 m 2 ) [ 21 ], both higher when compared with the levels in the dialysis population studied by van Biesen et al [ 20 ]. Other markers related to FO, such as N-terminal prohormone brain natriuretic peptide (NT-pro-BNP) and vena cava diameter, were higher in CKD stage 5 when compared with CKD stage 3–4 patients [ 17 ].…”
Section: Cardiovascular Parametersmentioning
confidence: 99%
“…This association persisted after controlling for eGFR, suggesting mechanisms other than decreased renal clearance of NT‐pro‐BNP. Volume overload is a poor prognosticator in CKD, and despite decreased renal clearance of BNP or NT‐pro‐BNP in later stage CKD, elevated levels in earlier stages may reflect subclinical chronic volume overload in the setting of albuminuria . While hs‐TnT more specifically prognosticated cardiovascular outcomes, BNP was associated with both cardiovascular outcomes and all‐cause death, supporting this underlying pathophysiologic mechanism of chronic volume overload secondary to albuminuria even before decline in GFR.…”
Section: Discussionmentioning
confidence: 91%